Kritik Rasial dalam Proposisi Ester 4:4-17 sebagai Diasporic Novella - Tansul, Tandri (SEKOLAH TINGGI AGAMA KRISTEN TERUNA BHAKTI, 2023)
The Book of Esther is a book whose theological significance is difficult to find. This is part of the controversial Old Testament megillot book from the early days of the canonization process to the present day with various interpretations, especially in interpreting God's presence amid turbulent conflicts of the people as a diaspora community. Esther 4:4-17 describes Mordhekai's plea to Esther to help Jews threatened by Haman's racial treatment as a representative of the Amalekites. This article aims to discover the theology of the Book of Esther through the analysis of Esther 4:4- 17 as a controlling story under the theme of racial criticism struggles among diaspora groups. The method used is the analysis of the structure of the story's meaning, paying attention to the plot controlling the story. The result is that the meaning of the story includes the treatment of the Jewish people that ends in the threat of genocide; king Xerxes' strategy to expand his power; Mordhekai and Esther's strategy in racial treatment; there will be God's help during silence; and there will be freedom for the Jews. The placement of God is active in the drama of people's lives, even in hidden impressions. On the side of social-political efforts, the reading of this paper reveals racial equality even though living under the ruler. Abstrak Kitab Ester merupakan kitab yang sulit untuk ditemukan makna teologisnya. Sebagai bagian dari kitab Megillot dalam Perjanjian Lama yang kontroversial dari masa awal proses kanonisasi sampai kini, dengan beragam penafsiran, khususnya dalam menafsirkan kehadiran TUHAN di tengah gejolak konflik umat sebagai komunitas diaspora. Ester 4:4-17 menuliskan mengenai permohonan Mordhekai kepada Ester untuk menolong orang-orang Yahudi yang terancam karena perlakuan rasial Haman sebagai wakil dari orang-orang Amalek. Pendekatan yang berbeda tentu menghasilkan pesan teologi yang beragam pula. Tujuan penulisan artikel ini ialah untuk menemukan teologi Kitab Ester melalui analisis Ester 4:4-17 sebagai cerita pengendali di bawah tema perjuangan kritik rasial di tengah kelompok diaspora. Metode yang digunakan ialah analisis struktur makna cerita dengan memerhatikan alur pengendali cerita. Hasilnya ialah bahwa pemaknaan cerita yang meliputi perlakuan rasial bagi bangsa Yahudi yang berakhir dengan ancaman genosida; strategi raja Ahasyweros untuk meluaskan kekuasaannya; strategi Mordhekai dan Ester di tengah perlakuan rasial; pertolongan Tuhan di tengah kebisuan; dan ada kebebasan bagi orang Yahudi. Penempatan Tuhan yang aktif dalam drama kehidupan umat, sekalipun dalam kesan tersembunyi. Di sisi perjuangan politik sosial, pembacaan tulisan ini mengungkapkan kesetaraan rasial sekalipun hidup di bawah sang penguasa.